Peningkatan Kualitas Pembelajaran Matakuliah Calculus I Kelas SBI Menggunakan Model Pembelajaran Multi Media Interaktif (MMI) (Kreano, Jurnal Matematika Kreatif-Inovatif, 2011)
Calculus is a finite mathematics concepts to solve infinite mathematics problems. The subject which is given to students grade 1 and 2 semester, is a basic science to understanding the other subject on education mathematic program, Mathematics and science department, teacher training and education faculty, Sebelas Maret University. Learning of Interactive Multimedia (MMI) is one of learning model based IT which can be used in Calculus I learning. This learning model have aim to enhance concept mastery and to improve the learning attitude of students a multimedia interactive based tutorial model of Calculus I is applied. This research is quasi experimental with subject on SBI class from the faculty of teacher training and education Sebelas Maret University with mathematical education as a experiment class and physic education as a control class. Research data were collected by using a concept mastery pretest, posttest and a questionnaire. Data analysis was conducted by using t –test. The result of this research show that the MMI learning have significance on improve Calculus learning quality and also improve the learning attitude of students. Keywords: Calculus; Interactive multimedia; learning attitude